Equality, Diversity and Inclusion characteristics measured or reported in randomised trials of intrapartum interventions: A Scoping Review [version 1; peer review: 2 approved] - Aoife Smith; John Gilmore; Susan Hannon; Valerie Smith (HRB Open Research)
Background Equality, diversity and inclusion (EDI) has gained discursive momentum across multiple arenas, including in maternal health research. As a preliminary exploration for future discussion and development, we undertook a scoping review to identify the types, frequency, and extent of EDI characteristics that were measured and reported in randomised controlled trials (RCTs) of intrapartum interventions specifically. Methods Joanna Briggs Institute methodological guidance for scoping reviews guided the conduct of the review. The population were women of any parity and risk category who were enrolled in intrapartum RCTs in any birth setting or geographical location. The concept was measured and reported EDI characteristics. CINAHL, MEDLINE, PsycINFO, EMBASE, and CENTRAL were searched from January 2019 to March 2024. Data were extracted using a pre-designed form. The findings were summarised and narratively reported supported by illustrative tables and graphs. Results Two-hundred and forty-seven RCTs from 49 countries were included. Eleven EDI characteristics were measured or reported in at least one RCT, although frequency varied. Religion, for example, featured in three RCTs only, whereas Age featured in 222 RCTs. How the EDI characteristics featured also varied. Race/Ethnicity, for example, was described in 21 different ways in 25 RCTs. Similarly, Education was reported in 62 different ways across 96 RCTs. Ninety RCTs limited inclusion to nulliparous participants only, six RCTs required participants to have a minimum educational level, 127 RCTs had inclusion age cut-offs although 23 different variations of this were noted and 15 RCTs excluded participants on the grounds of disability. Conclusions This scoping review highlights EDI characteristic measurement and reporting deficits in intrapartum RCTs. There is a critical need for improvements in designing, conducting, and reporting RCTs to incorporate EDI. By adopting more extensive EDI practices a greater understanding of healthcare treatments and innovations leading to enhanced maternal health equity could be achieved.